Сучасні зарубіжні підходи до розуміння лідерства і виховання лідерів - Галузяк, Василь; Акімова, Ольга; Громов, Євген (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуті сучасні зарубіжні підходи до розуміння лідерства та виховання лідерів. З’ясовано, що у сучасній зарубіжній організаційній психології все більшої популярності набувають прогресивні моделі лідерства, які приходять на зміну традиційним центрованим на лідері підходам. Наявність різних поглядів на сутність і призначення лідерства зумовлює існування множинності підходів до виховання лідерів. Виокремлено дві моделі підготовки лідерів – нормативно-адаптивну і особистісно-розвивальну, які відрізняються за своїми завданнями і способами реалізації. Кожна модель має свої переваги та обмеження і за певних умов може виявитися ефективною. Загальна стратегія має полягати у тому, щоб з урахуванням конкретних обставин знаходити оптимальний баланс нормативно-адаптивної і особистісно-розвивальної моделей, що зробить можливою виховання лідерів нового покоління, здатних не просто керувати підлеглими, а сприяти їх особистісному зростанню, об'єднувати їх навколо спільної мети і надихати на здійснення позитивних змін у суспільстві.

Contemporary foreign approaches to understanding leadership and education and upbringing future leaders have been considered. It’s been revealed that in the modern foreign organizational psychology, progressive models of leadership, which replace the traditional leader-centered approaches, are becoming increasingly popular. This transformation is primarily conditioned by transition from industrial to postindustrial paradigm of development, which significantly increases the role of information, intelligence and innovation in all spheres of life. Progressive leadership concepts are characterized by a number of features reflecting changes in interpretation of this complex phenomenon: considering leadership not as an individual influence of a leader on his subordinates, but as a kind of relationship in which an important role is assigned to the leader’s followers; transition from compet-itive transactional leadership to cooperative transformative one; enhancement the leader’s educational function. The presence of different views on leadership nature and purpose causes the existence of different approaches to the leaders’ education. The analysis of differences in leadership understanding within traditional and progressive concepts enabled to distinguish between two leader training models – normatively-adaptive and personally-developing, differing in their tasks and methods of implementation. Both models have their advantages and limitations and can be effective under certain conditions. Taking into account specific circumstances, the general strategy lies in finding the optimal balance of normatively-adaptive and personally-developing models, making possible upbringing the new generation leaders, who are able not only manage subordinates, but also contribute to their personal growth, bringing them together around common goals, and inspiring for making positive changes in society.
Modern foreign approaches to understanding leadership and upbringing leaders
Keywords: зарубіжні моделі виховання лідерів; нормативно-адаптивна модель; особистісно-розвивальна модель; foreign model of education of leaders; normatively-adaptive model; personally-developing model